2021
DOI: 10.1007/s13300-021-01038-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cardiovascular and Renal Co-morbidities in Patients with Type 2 Diabetes in the Gulf, a Cross-sectional Observational Study

Abstract: Introduction: Understanding comorbid conditions with type 2 diabetes mellitus (T2DM) is critical for clinical decision-making regarding the choice of pharmacotherapy. This study aimed at describing the prevalence and coprevalence of comorbidities, including chronic kidney disease (CKD) and cardiovascular disease (CVD) (coronary artery disease (CAD), cerebrovascular disease, peripheral arterial disease (PAD) and congestive heart failure (CHF)) among patients with T2DM. Methods: A cross-sectional multi-center ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
(25 reference statements)
1
11
0
Order By: Relevance
“…The most common types of comorbidities identified in this study were also consistent with previous findings [31] , [32] . The relatively high prevalence of diabetes and related comorbidities creates the perfect storm for poor outcomes in patients with COVID-19 infection.…”
Section: Discussionsupporting
confidence: 92%
“…The most common types of comorbidities identified in this study were also consistent with previous findings [31] , [32] . The relatively high prevalence of diabetes and related comorbidities creates the perfect storm for poor outcomes in patients with COVID-19 infection.…”
Section: Discussionsupporting
confidence: 92%
“…24 Another multinational study (CAPTURE) showed that people with T2DM and established CVD (33%) have a higher burden of renal dysfunction (microalbuminuria [31.8% vs 20.6%], macroalbuminuria [10 prevalent comorbidities in T2DM. 26 People with T2DM have almost quadruple the risk (hazard ratio [HR] 3.77, P = .001), while those with coronary heart disease are 2.47 (P = .004) times more likely to develop CKD stages 3-5. 27 A multinational registry of T2DM reported that cardiorenal disease was consistently the most frequent first manifestation (60%), stemming from 24% HF and 36% CKD, with HF being associated with a 2-fold risk of CKD and vice versa.…”
Section: Burden and Associated Risk Factors For Cardiorenal Complicat...mentioning
confidence: 99%
“…Another multinational study (CAPTURE) showed that people with T2DM and established CVD (33%) have a higher burden of renal dysfunction (microalbuminuria [31.8% vs 20.6%], macroalbuminuria [10.8% vs 6.8%], and estimated glomerular filtration rate [eGFR] of ≤ 59 mL/min/1.73 m 2 [30.7% vs 15.4%]) compared to those without CVD 25 . CKD (44.3%) and CVD (17.3%) are the most prevalent comorbidities in T2DM 26 . People with T2DM have almost quadruple the risk (hazard ratio [HR] 3.77, P = .001), while those with coronary heart disease are 2.47 ( P = .004) times more likely to develop CKD stages 3‐5 27 .…”
Section: Burden and Associated Risk Factors For Cardiorenal Complicat...mentioning
confidence: 99%
See 2 more Smart Citations